COLONIAL AMERICA AND THE QUESTION OF LEGITIMACY - AHOUANGANSI, S. Raoul; KOMBIENI, Didier (My University, 2020)
The question of legitimacy in colonial America provokes enormous controversies among Americans. The conception of the right to command and the duty to obey varies in interpretations from one social group to another one. What is law and what is not, create dramatic frustrations and contentions even among founding fathers, from Declaration of Independence to federal Constitution. This article intends, basing on contents analysis as a scientific method in empiric researches, to demonstrate how Americans succeeded in detecting and acknowledging ‘the people’ as the be-all and end-all in field of legitimacy
Keywords: legitimacy; Americans; contentions; social group; the people.